HARMONIC QUARTET OF POINTS: GEOMETRIC PROPERTIES AND APPLICATIONS - Mahmudjonova Dilrabo Móminjon qizi, Dilnoza Xaytmirzayevna Maxmudova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper analyzes the concept of the harmonic quartet of points, its fundamental geometric properties, and practical applications. The harmonic ratio provides a deeper understanding of geometric relationships, and its use in solving various mathematical problems is discussed. Furthermore, the connections between harmonic division and modern computational geometry are explored.